2020
DOI: 10.1097/md.0000000000019034
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D and prediabetes

Abstract: Background: Previous studies showed conflicting results for associations between vitamin D and prediabetes. The study aimed to make a systematic review and meta-analysis for the association between vitamin D and prediabetes. Methods: We searched for articles identifying associations between vitamin D and prediabetes published in English until July 2019 in following databases (PubMed, Web of Science, EMBASE, Medline, Google Scholar, and Cochrane database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…Based on the serum levels of 25(OH)D, vitamin D nutritional status has been classified as deficient (<20 ng/mL), insufficient (21-29 ng/mL), and sufficient (>30 ng/mL) [2]. Recent evidence has shown an association of vitamin D deficiency with several metabolic disturbances such as metabolic syndrome (MetS), high blood pressure (BP), type 2 diabetes (T2D), insulin resistance (IR), and obesity [14][15][16][17][18]. Diverse studies have suggested that vitamin D deficiency could promote adipogenesis and disturb the metabolism involved in energy homeostasis, such as leptin, adiponectin, and resistin [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the serum levels of 25(OH)D, vitamin D nutritional status has been classified as deficient (<20 ng/mL), insufficient (21-29 ng/mL), and sufficient (>30 ng/mL) [2]. Recent evidence has shown an association of vitamin D deficiency with several metabolic disturbances such as metabolic syndrome (MetS), high blood pressure (BP), type 2 diabetes (T2D), insulin resistance (IR), and obesity [14][15][16][17][18]. Diverse studies have suggested that vitamin D deficiency could promote adipogenesis and disturb the metabolism involved in energy homeostasis, such as leptin, adiponectin, and resistin [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effects of vitamin D on insulin sensitivity have been inconsistent [34,35]. Although it has been proposed that vitamin D deficiency plays an important role in IR [36], many factors are involved, including age, obesity and the presence of prediabetes as well as other cardiovascular risk factors [37]. Inconsistent results between vitamin E and IR have also been reported [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…A four-year followup study suggested that low levels of serum 25(OH)D might be linked to the increased incidence of prediabetes or T2DM in Chinese individuals [5]. Two meta-analyses observed that the administration of vitamin D led to a reduction in glucose and hemoglobin A1c (HbA1c), regardless of intramuscular injection and oral supplementation [6,7]. Therefore, more randomized controlled trials (RCTs) are needed to explore the association between vitamin D supplementation and prediabetes.…”
Section: Introductionmentioning
confidence: 99%